Pengaruh Pendapatan Orang Tua, Gaya Hidup Terhadap Konsumsi Mahasiswa Pendidikan Matematika UIN Alauddin Makassar - Nur Yuliany (Movere Journal, 2026)
This study aims to reveal the influence of parental income and lifestyle on the consumption behavior of students in the Mathematics Education Study Program at UIN Alauddin Makassar. A quantitative approach with an ex-post facto design of associative causal nature was employed. The study involved 49 students selected using the Proportionate Stratified Random Sampling technique. The research instrument was a closed-ended questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics and multiple linear regression with the assistance of SPSS version 24. The findings indicate that both parental income and lifestyle have a positive and significant effect on student consumption, both partially and simultaneously. The coefficient of determination (R²) of 0.832 shows that 83.2% of the variation in student consumption can be explained by these two variables. These findings suggest that increased parental income and a tendency toward a consumptive lifestyle contribute to higher levels of student consumption.